Taoism and self knowledge : the chart for the cultivation of perfection (Xiuzhen tu) - Despeux, Catherine (Sinica Leidensia, 2019)
"Catherine Despeux's book is a study of the Internal Alchemical text "Chart for the Cultivation of Perfection." It begins with an analysis of pictographic and symbolic representation of the body in early Taoism after which the author examines different extant versions of the "Chart" as it was transmitted among Quanzhen groups in the Qing dynasty. The book is comprised of four main parts: the principal parts of the body and their nomenclature in Internal Alchemy, the spirits in the human body, and the alchemical processes and procedures used in thunder rituals and self-cultivation. This is a revised, expanded edition of the original French edition Taoïsme et connaissance de soi. La carte de la culture de la perfection (Xiuzhen tu) Paris, 2012"--